Voluntary teacher work at higher education: precariousness of work conditions in Argentina, Brazil and Chile - Gomes Melo, Savana Diniz; Gomes, Suzana dos Santos (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
Teacher work has passed through deep transformations resulting from successive and engendered education reforms promoted in Higher Education in the last decades, which seek to meet the demands of capitalism. In that process has been observed the appearing or increasing of voluntary teacher work. This fact has driven studies about that theme. The present paper offers a contribution towards that means, exposing the experience with that type of work in three countries: Argentina, Brazil and Chile. Beginning with a literature review, the exploratory study this paper resulted from consisted of interviews with teachers from those countries. The guiding presupposition of the study takes voluntary teacher work as a contribution, among many, for the precariousness and the intensification of teacher work at the universities. The interviews point out elements that ratify such presupposition and evince the need for theoretical amplification and deepening about the theme and its articulation to the transformation of work in general, in contemporary capitalism.